Deportasi Terhadap Warga Amerika Serikat Penduduk Chagossia Ditinjau dari Persepektif Hukum Pidana Internasional - Lutfiah Fitri Yani; Regina Eka Anggraeni (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This journal article was created with the aim of knowing the conditions and how the deportation carried out by the United States against the population of Chagossia will be viewed from the perspective of International Criminal Law, then what is the perspective of International Criminal Law in the case of the United States' deportation of the population of Chagossia. In fact, deportation itself is widely known to the public, at least to certain groups of people, especially legal experts. It is written in article 1 number 36 in Law no. 6 of 2011 concerning Immigration, which essentially refers to deportation, is a forced action to remove a foreigner from the territory of a country for the reason that the foreigner is not wanted in its territory by the country concerned.